Edith Meiser as The Woman of the Sherlock Holmes interwar radio serial. Issue 1 (2nd January 2023) - Johnsen, Rosemary Erickson
ABSTRACT: When American actress Edith Meiser (1898–1993) initially proposed the idea of Sherlock Holmes radio adaptations for an American audience in 1930, she was told it was "too old-fashioned" and prospective sponsors "wanted a streamlined sleuth." She persisted, and the series ran from 1930 to 1948 (with some breaks). During its run, when the Conan Doyle estate tightly controlled any use of Sherlock Holmes material, the series earned Meiser the distinction of being the author of more original Sherlock Holmes stories than anyone apart from Arthur Conan Doyle himself. Grounded in archival research in the Sherlock Holmes Collections at the Andersen Library, University of Minnesota, Twin Cities, this article argues that Meiser's radio scripts translating Holmes and Watson into the medium of the interwar radio serial represent a significant yet overlooked contribution to intermodernist literature and culture.